2015
DOI: 10.1097/aog.0000000000000760
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Human Papillomavirus Infection and Cervical Cytology in Women Using Copper-Containing and Levonorgestrel-Containing Intrauterine Devices

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Conversely, administration of agonist anti-CD40 mAb to LNG-treated mice at dpi 1 produced Chlamydia burden and pulmonary inflammation at 12 dpi that closely resembled that seen in placebo-pelleted controls. Thus, while our use of sustained-release LNG pellets in a mouse model of respiratory C. trachomatis infection may not fully recapitulate the immunomodulatory effects of LNG-IUS use in the genital tract of women, the elevated chlamydial burden we detected in LNG-treated mice at 12 dpi is entirely consistent with the delayed eradication of genital HPV observed in women using LNG-IUS12.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Conversely, administration of agonist anti-CD40 mAb to LNG-treated mice at dpi 1 produced Chlamydia burden and pulmonary inflammation at 12 dpi that closely resembled that seen in placebo-pelleted controls. Thus, while our use of sustained-release LNG pellets in a mouse model of respiratory C. trachomatis infection may not fully recapitulate the immunomodulatory effects of LNG-IUS use in the genital tract of women, the elevated chlamydial burden we detected in LNG-treated mice at 12 dpi is entirely consistent with the delayed eradication of genital HPV observed in women using LNG-IUS12.…”
Section: Discussionmentioning
confidence: 71%
“…Among the 66 women in that study diagnosed with high-risk HPV genital infection prior to IUS insertion, 70% initiating copper-containing IUS use vs. 42% initiating LNG-IUS use cleared infection during the first year after insertion12. Such results implied LNG, and not the mere presence of an IUS, was the variable more closely associated with delayed HPV clearance.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The studies included in the meta-analyses were mostly older studies, which suggests these women were more likely copper-IUD users. One study has suggested that the effect on hrHPV biology may be different, in which copper-IUD users were more likely to clear hrHPV infections than levonorgestrel-releasing IUD users [15]. A caseecontrol study with recent IUD use also found a trend toward a protective effect of copper-IUDs, but an increased risk of CIN2þ for levonorgestrel-releasing IUDs [12].…”
Section: Parametersmentioning
confidence: 99%
“…Other studies have suggested that the effect of these IUDs on HPV biology may be different. 15 Our study was conducted among young women in the US, and most of the IUD use was in the late 2000s, therefore many of our IUD users were likely using LNG-releasing IUDs. Older studies, including the meta-analysis showing that IUDs are associated with decreased risk of cervical cancer, 4 likely included mostly copper IUDs.…”
Section: Commentmentioning
confidence: 99%